2017
DOI: 10.2217/cer-2016-0089
|View full text |Cite
|
Sign up to set email alerts
|

Cost–effectiveness analysis of endoscopic eradication therapy for treatment of high-grade dysplasia in Barrett’s esophagus

Abstract: Aim:The aim was to evaluate the cost-effectiveness of endoscopic eradication therapy (EET) with combined endoscopic mucosal resection and radiofrequency ablation for the treatment of high-grade dysplasia (HGD) arising in patients with Barrett's esophagus compared with endoscopic surveillance alone in the UK. Materials & methods:The cost-effectiveness model consisted of a decision tree and modified Markov model. A lifetime time horizon was adopted with the perspective of the UK healthcare system. Results: The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(63 reference statements)
1
4
0
Order By: Relevance
“…The results of this study align with the previous literature which has shown RFA to be cost effective for LGD and HGD separately [22,25,39]. Although the previous analysis of RFA for only HGD patients resulted in a marginally lower ICER (£1,272) [39], the current analysis highlights that use of RFA for both LGD and HGD patients remains significantly cost-effective (ICER: £3,006). Although, NICE clinical guidelines reported ICERs far in A c c e p t e d M a n u s c r i p t excess of the current results (£24,829 [3]).…”
Section: Accepted Manuscript 4 Discussionsupporting
confidence: 88%
“…The results of this study align with the previous literature which has shown RFA to be cost effective for LGD and HGD separately [22,25,39]. Although the previous analysis of RFA for only HGD patients resulted in a marginally lower ICER (£1,272) [39], the current analysis highlights that use of RFA for both LGD and HGD patients remains significantly cost-effective (ICER: £3,006). Although, NICE clinical guidelines reported ICERs far in A c c e p t e d M a n u s c r i p t excess of the current results (£24,829 [3]).…”
Section: Accepted Manuscript 4 Discussionsupporting
confidence: 88%
“…In addition to the clinical studies, four cost–utility analyses were identified. 68 76–78 They reported that at a threshold of £20 000 per QALY gained, EMR combined with RFA was cost effective versus endoscopic surveillance 77 ; EMR plus RFA plus surveillance, EMR plus APC plus surveillance and surgery were all cost effective versus no surveillance 78 ; RFA followed by endoscopic surveillance was cheaper and more effective than oesophagectomy 76 ; and RFA alone was cheaper and more effective than oesophagectomy. 68 …”
Section: Consultationmentioning
confidence: 99%
“…In addition to the clinical studies, four cost-utility analyses were identified. 68 76-78 They reported that at a threshold of £20 000 per QALY gained, EMR combined with RFA was cost effective versus endoscopic surveillance 77 ; EMR plus RFA plus surveillance, EMR plus APC plus surveillance and surgery were all cost effective versus no surveillance 78 ; RFA followed by endoscopic surveillance was cheaper and more effective than oesophagectomy 76 ; and RFA alone was cheaper and more effective than oesophagectomy. 68 Based on clinical experience the committee recommended that high-grade dysplasia should be endoscopically resected, when oesophageal lesions are visible at endoscopy, and the residual Barrett's oesophagus should be treated with endoscopic ablation.…”
Section: Managing High-grade Dysplasia and Stage 1 Oesophageal Adenoc...mentioning
confidence: 99%
“…The endpoint of surveillance is the detection of dysplasia or intramucosal carcinoma (IMCa). Endoscopic eradication therapy (EET) for high‐grade dysplastic (HGD) lesions and early neoplasia within BE has been shown to be cost‐effective and eliminates the need for esophagectomy 9,10 . Expert agreement on quality indicators for EET for BE has been published and outlines some guidance for those wishing to establish such a service 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic eradication therapy (EET) for high-grade dysplastic (HGD) lesions and early neoplasia within BE has been shown to be cost-effective and eliminates the need for esophagectomy. 9,10 Expert agreement on quality indicators for EET for BE has been published and outlines some guidance for those wishing to establish such a service. 11 The statements are supported by evidence and give direction to those treating BE associated dysplasia and malignancy, while affording operators latitude on their approach to endoscopic resection (ER) and ablation.…”
Section: Introductionmentioning
confidence: 99%